MORPHOLOGICAL STRUCTURE OF HEPATOCYTES AT ASEPTIC INFLAMMATION OF PERITONEUM IN RATS - Voloshina, E.V.; Shepitko, V.I. (World of Medicine and Biology, 2018)
The main cells which carry out all basic functions of a liver are hepatocytes. Functional activity of hepatocytes is shown in their participation in absorption, synthesis, accumulation and chemical transformation of different substances which can be allocated further in blood or bile [4, 5]. The aim of work Considering different functional activity of hepatocytes and their important role in accumulation and a conclusion of harmful agents, modelling of an aseptic peritonitis with the subsequent studying of hepatocytes reaction during the different periods of experiment on rats [1, 2] was the aim of our work. Materials and research methods Research has been carried out on 50 adult rats - males of a line "Vistar", in weight of 180-200 g. Animals were in conditions of vivarium of HSEEU «Ukrainian medical stomatologic academy» which to the experiment beginning kept at a natural light mode on a standard diet ad libitum. Experiments have been executed in the autumn that there was no influence of biological activity of daily and seasonal rhythms, after last feeding in 18 hours, in the morning. Healthy rats were exposed to experiments only. Experimentally liver slices were taken, hepatocytes of which were object of research. Experimental animals, according to the planned problems, have been divided into two groups. The first group included control group of animals which was 5. Other group had been simulated a sharp experimental peritonitis (EP). Disease caused by intraperitoneal introduction of 5 mg λ-carrageenan (Sigma, USA) with which planted in 1 ml of an isotonic solution of sodium chloride per 1 animal, such animals was 45. Experimental research carried out to following terms: for 1, 2, 3, 5, 7, 10, 14, 21 and 30 days. Applied general histological, morphometric and electron microscopic methods of research. Histological examination of hepatocytes was performed after the manufacture of paraffin sections. Liver fragments were fixed in 10% formalin solution. Subsequently, the specimen fragments were dehydrated in alcohols of increasing concentration: they started at 50º and ended with 96º ethyl alcohol. Chloroform was an intermediate medium. Liver fragments were poured twice with a mixture of paraffin and wax, replaced the mixture once. Preparations were stained with hematoxylin and eosin for histological and morphological studies [3]. Hepatocytes reaction on an aseptic inflammation has been revealed for 1 and 2 days during experiment. In a reactive phase of peritonitis the liver structure is kept. Hepatic segments: the central veins were moderately plethoric, contained a considerable quantity of erythrocytes. Sinusoids lumina were non-uniformly appeared through and were free from erythrocytes. The structure of hepatocytes was different: in the majority of nucleus cells outlined, but they had the different form and intensity of colouring. The kept nuclei were with signs of karyopyknosis or karyolysis, the granular dystrophy of cytoplasm was observed. The beam structure of hepatic segment has been kept. Bilious channels of usual form, lined with cubic epithelium and are moderately infiltrated wyth a lymph-histiocytic infiltrate. Strom of portal paths has been presented by a vascular component and insignificant limph-histiocytic infiltrate. The hypostasis of Disse spaces, sinusoids and the central veins hyperemia were observed. For 5 days during experiment in a toxic phase of a peritonitis two types of changes in hepatocytes were observed. The structure of one group of hepatocytes was in a stage of functional pressure. High functional activity of Kupffer cells to which testified has been revealed: well developed granular endoplasmic reticulim, the hypertrophied Golgi complex, numerous lysosomes. Hepatocytes in the second group have undergone to dystrophic and destructive infringements, the nuclear membrane had the centre of destruction. For 7-14 days of experiment the terminal phase of a peritonitis developed. It was characterised by cytoplasm coagulation of hepatocytes, in some hepatocytes there was a centre of a granular dystrophy of cytoplasm, for 7 days there was cytoplasm hydropic degeneration, a sludge-phenomenon; in some hepatocytes appeared vacuoles, filled with a translucent liquid, veins hyperemia. 14 days of experiment were characterised by total disintegration of hepatocytes cytoplasmatic organelles, separate parts had zones of lysis, perinuclear spaces are expanded, lumpy disintegration of hepatocytes cytoplasm, a thrombosis of the central vein, sinusoids hyperemia. Appeared hyperplasia of plasmatic grid in which zone there were separate glycogen granules. For 21 days of experiment crushing lesion had the majority of hepatocytes which were characteristic for in agony cells: desolation of cytoplasm, presence of huge vacuoles in perinuclear zone. Have been also destructively changed endotheliocytes of sinusoid capillaries: the centre of lysis, huge vacuoles. Only Kuppfer cells were able functional activity. Conclusions Thus, the experimental researches have shown that the morphological condition of liver in rats after modelling of an aseptic peritonitis considerably changes. Histologic and electronic microscope research has shown that in reactive phase of a peritonitis dystrophic changes of hepatocytes and sinusoids endotheliocytes developed. These reversible changes are proved by adaptable reaction of cells to inflammation and intoxication processes. In toxic and especially in terminal peritonitis phases in submicroscopic architectonics of hepatocytes and endotheliocytes of sinusoid capillaries along with dystrophic changes there were destructive infringements of cells organelles which have appeared irreversible.